# Find the derivative of f(x) = 1+tan(x) / 1-tan(x)

### 2 Answers | Add Yours

We need to know the following trigonometric function here.

`cos2x = cos^x-sin^2x`

`sin2x = 2sinxcosx`

`sin^2x+cos^2x = 1`

`(1+tanx)/(1-tanx)`

`= (1+tanx)/(1-tanx)xx(1+tanx)/(1+tanx)`

`= (1+tanx)^2/(1-tan^2x)`

`= (1+sinx/cosx)^2/(1-(sin^2(x))/(cos^2(x)))`

`= ((cosx+sinx)^2/(cos^2x))/((cos^2x-sin^2x)/(cos^2x))`

`= (cosx+sinx)^2/(cos^2x-sin^2x)`

`= (cos^2x+sin^2x+2sinxcosx)/(cos2x)`

`= (1+sin2x)/(cos2x)`

`f(x) = (1+tanx)/(1-tanx) = (1+sin2x)/(cos2x)`

`f'(x)`

`= (cos2x*2cos2x-(1+sin2x)(-2sin2x))/(cos^2(2x))`

`= (2(cos^2(2x)+sin^2(2x)+sin2x))/(cos^2(2x))`

`= (2(1+sin2x))/(cos^2(2x))`

`= (2(1+sin2x))/(1-sin^2(2x))`

`= (2(1+sin2x))/((1+sin2x)(1-sin2x))`

`= 2/(1-sin2x)`

** So the derivative of f(x) is** `f'(x)= 2/(1-sin2x)`

**Sources:**

You should use the quotient rule such that:

`f'(x) = ((1 + tan x)'(1 - tan x) + (1 + tan x)(1 - tan x)')/((1 - tan x)^2)`

`f'(x) = ((1/(cos^2 x))(1 - tan x) + (1 + tan x)(-1/(cos^2 x)))/((1 - tan x)^2)`

`f'(x) = (1/(cos^2 x) - tan x/(cos^2 x) - 1/(cos^2 x) -tan x/(cos^2 x))/((1 - tan x)^2)`

`f'(x) = (- 2tan x/(cos^2 x))/((1 - tan x)^2)`

Hence, evaluating the derivative of the function using the quotient rule yields `f'(x) = (- 2tan x/(cos^2 x))/((1 - tan x)^2).`